1981
DOI: 10.1104/pp.68.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Inhibition of Phytochrome-Induced Germination in Potentilla norvegica L. Seeds

Abstract: changes affecting germination when compared to our earlier results (8). Methods used were described previously (8), with the exception that the seeds were planted in 125-ml flasks containing a disc of 5.5 cm, Whatman No. 2 filter paper, and 1.5 ml water. Germination cabinets were held at + 1°C of the indicated temperature. Flasks were sealed with rubber serum stoppers through which an amount of ethylene in I ml of a stock preparation could be injected to achieve the desired concentration. Venting of the flask … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In many species the inhibition of seed germination due to dormancy or stress conditions can be completely or partially reversed by C 2 H 4 or ethephon (Kepczynski and Kepczynska, 1997), which indicates that seeds have a C 2 H 4 response mechanism. Ethylene may be loosely associated with a site required for phytochrome action (Suzuki and Taylorson, 1981). Trujillo et al, (2008) reported that SodERF3, a novel sugarcane ethylene responsive factor (ERF), enhanced salt and drought tolerance when over expressed in tobacco plants.…”
Section: Introductionmentioning
confidence: 99%
“…In many species the inhibition of seed germination due to dormancy or stress conditions can be completely or partially reversed by C 2 H 4 or ethephon (Kepczynski and Kepczynska, 1997), which indicates that seeds have a C 2 H 4 response mechanism. Ethylene may be loosely associated with a site required for phytochrome action (Suzuki and Taylorson, 1981). Trujillo et al, (2008) reported that SodERF3, a novel sugarcane ethylene responsive factor (ERF), enhanced salt and drought tolerance when over expressed in tobacco plants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ethylene can accelerate germination in cold-stratified seeds of Echinacea angustifolia (Macchia et al 2001). In contrast, seeds of several other wetland plants (Echinochloa crus-galli, Digitaria sanguinalis, Ipomoea purpurea, Persicaria pensylvanica) remained unresponsive to ethylene treatment (Taylorson, 1979), whereas in Chenopodium rubrum, Plantago major, P. maritima and Potentilla norvegica seed germination is inhibited (Olatoye & Hall, 1973;Suzuki & Taylorson, 1981). Yet, although the physiological effects of ethylene on seed germination are well studiedit promotes seed germination through antagonistic interaction with abscisic acid (ABA) and synergistic action with gibberellins (GAs; Ahammed et al 2020)its ecological role as a seed germination trigger is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The germinatioti of some seeds is stimulated by C2H4 (Toole, Bailey & Toole, 1964;Abeles & Lonski, 1969;Esashi & Leopold, 1969;Egley, 1972;Schonbeck & Egley, 1981). In other seeds, however, G2H4 inhibits germination (Olatoye & Hall, 1972;Suzuki & Taylorson, 1981). An unsolved, important problem is whether such a different mode of action of C2H4 is only determined genetically or can be controlled by conditioning.…”
Section: Introductionmentioning
confidence: 99%